(-4)-?=(-9)
?-(-2)=
?-(-6)=(-2)
12-?=(-6)
2-?=(-32)
(-4)-?=?
32+(-18)-42=
45-(-5)+(-20)=
-21-(-29)-32=
-16+(-14)-(-17)=
-41+52-(-26)=
-18+39+(-9)=
6x(-2):12x(-2)=
-2 1/2x8-(-5)x(-2/15)=
-17x3+7x(-13):(-7)=
-6x9-(-36):4=
-12:6x(-4):2=
?x(-1)x?x2x?x(-1)=-72
-2x?x5x?x(-1)=-160
-2x?x5x?x(-1)=320
-3x4x?x(-5)=180

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-10-01T20:55:33+02:00
(-4)-?=(-9)
?-(-2)= brakuje wyniku, więc niewiadomo co wstawić
-8-(-6)=(-2)
12-18=(-6)
2-34=(-32)
(-4)-5=(-9)
32+(-18)-42=-28
45-(-5)+(-20)=30
-21-(-29)-32=-24
-16+(-14)-(-17)=-13
-41+52-(-26)=37
-18+39+(-9)=12
6x(-2):12x(-2)=-12: (-24)=1/2
-2 1/2x8-(-5)x(-2/15)=-20-2/3=19 1/3
-17x3+7x(-13):(-7)=-51+13=-38
-6x9-(-36):4=-54+9=63
-12:6x(-4):2=4
(-2)x(-1)x2x2x9x(-1)=-72
-2x8x5x(-2)x(-1)=-160
-2x16x5x2x(-1)=320
-3x4x3x(-5)=180
2009-10-01T21:02:14+02:00
-4-5=-9
? nie napisałeś co ma wyjsc
(-8)-(-6)=-2
12-18=(-6)
2-34=(-32)
(-4)-?= to samo co wczesniej:(
32+(-18)-42=-28
45-(-5)+(-20)=30
-21-(-29)-32=-24
-16+(-14)-(-17)=-13
-41+52-(-26)=37
-18+39+(-9)=12
6x(-2):12x(-2)=2
-2 1/2x8-(-5)x(-2/15)=-254/3
-17x3+7x(-13):(-7)=-38
-6x9-(-36):4=-45
-12:6x(-4):2=4
-4x(-1)x3x2x3x(-1)=-72
-2x4x5x4x(-1)=-160
-2x4x5x8x(-1)=320
-3x4x3x(-5)=180